Integrated proteomics and phosphoproteomics revealed druggable kinases in neoadjuvant chemotherapy resistant tongue cancer - George, Irene A.; Sathe, Gajanan; Ghose, Vivek; Chougule, Anuradha; Chandrani, Pratik; Patil, Vijay; Noronha, Vanita; Venkataramanan, R.; Limaye, Sewanti; Pandey, Akhilesh; Prabhash, Kumar; Kumar, Prashant (Frontiers in Cell and Developmental Biology, 2022)
Tongue squamous cell carcinoma is an aggressive oral cancer with a high incidence of metastasis and poor prognosis. Most of the oral cavity cancer patients present in clinics with locally advanced unresectable tumors. Neoadjuvant treatment is beneficial for these individuals as it reduces the tumor size aiding complete resection. However, patients develop therapy resistance to the drug regimen. In this study, we explored the differential expression of proteins and altered phosphorylation in the neoadjuvant chemotherapy resistant tongue cancer patients. We integrated the proteomic and phosphoproteomic profiles of resistant (n = 4) and sensitive cohorts (n = 4) and demonstrated the differential expression and phosphorylation of proteins in the primary tissue of the respective subject groups. We observed differential and extensive phosphorylation of keratins such as KRT10 and KRT1 between the two cohorts. Furthermore, our study revealed a kinase signature associated with neoadjuvant chemotherapy resistance. Kinases such as MAPK1, AKT1, and MAPK3 are predicted to regulate the resistance in non-responders. Pathway analysis showed enrichment of Rho GTPase signaling and hyperphosphosphorylation of proteins involved in cell motility, invasion, and drug resistance. Targeting the kinases could help with the clinical management of neoadjuvant chemotherapy-resistant tongue cancer.